2012
DOI: 10.1155/2012/145754
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Evaluation of Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common cause of elevated liver function tests results, after the commonly investigated causes have been excluded, and frequently coexists with type 2 diabetes mellitus (T2DM) because the conditions have common risk factors. As both T2DM and NAFLD are related to adverse outcomes of the other, diagnosis and valuation of fatty liver is an important part of the management of diabetes. Although noninvasive methods, such as biomarkers, panel markers, and imaging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
190
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(202 citation statements)
references
References 159 publications
2
190
1
9
Order By: Relevance
“…Most of the western studies have reported the mean age of NAFLD between 41-45 years. In our cases NAFLD most commonly seen in the fourth and fifth decade, this is about a [5][6][7][8][9][10] years elder than what has been reported from other countries.…”
Section: Discussionmentioning
confidence: 74%
“…Most of the western studies have reported the mean age of NAFLD between 41-45 years. In our cases NAFLD most commonly seen in the fourth and fifth decade, this is about a [5][6][7][8][9][10] years elder than what has been reported from other countries.…”
Section: Discussionmentioning
confidence: 74%
“…In general, accumulation of lipids up to 5% of the liver weight results in the diagnosis of fatty liver disease or hepatic steatosis. In addition, if hepatic steatosis occurs in patients who do not consume alcohol on a daily basis, it is referred to as nonalcoholic fatty liver disease (NAFLD) [1] . Usually, NAFLD is classified as "primary" and "secondary", depending on the underlying etiology.…”
Section: Overview Of Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Based on available information, various researchers have proposed different hypotheses over time. The major hypotheses are as follows: (1) In 1998, Day et al [27] first proposed the "two-hit"…”
Section: Nafld Pathogenesismentioning
confidence: 99%
“…Zudem werden die Empfehlungen nach der Qualität ihrer Evidenz gewichtet: hoch (A), moderat (B) und gering (C). Nachfolgend sind nur die für die Diagnostik relevanten Empfehlungen zusammengefasst [16] [3,26,28]. Tabelle 5 stellt die bei NAFLD ausgewerteten Scores zusammen.…”
Section: Praxis-empfehlungen Zu Diagnostik Und Management Der Nafldunclassified